Inventory Management with Forecasting Method: Single Moving Average and Trend Projection - Amesanggeng Pataropura; Ivan Darmawan Sabatino; Riki Riki (Komunitas Dosen Indonesia, 2020)
Inventory management using forecasting methods aims to improve effectiveness and efficiency that facilitate trading businesses in the process of business transactions, improve delivery of information quickly, accurately, and transaction data properly and minimize errors. The system running in the system of selling goods is still manual, that is, it is not well computerized. The method used is forecasting which helps determine the estimated future stock of goods. Single Moving Average and Trend Projection. It can be concluded that the results of implementing this new system can assist trading businesses in recording transactions in the system. We can predict the current flow of goods which has been calculated based on 2 modules that have a connection with the system.